Blastocystis One Health Approach in a Rural Community of Northern Thailand: Prevalence, Subtypes and Novel Transmission Routes - Jinatham, Vasana; Maxamhud, Sadiya; Popluechai, Siam; Tsaousis, Anastasios D.; Gentekaki, Eleni (Frontiers in Microbiology, 2021)
Blastocystis is the most commonly found eukaryote in the gut of humans and other animals. This protist is extremely heterogeneous genetically and is classified into 28 subtypes (STs) based on the small subunit ribosomal RNA (SSU rRNA) gene. Numerous studies exist on prevalence of the organism, which usually focus on either humans or animals or the environment, while only a handful investigates all three sources simultaneously. Consequently, understanding of Blastocystis transmission dynamics remains inadequate. Our aim was to explore Blastocystis under the One Health perspective using a rural community in northern Thailand as our study area. We surveyed human, other animal and environmental samples using both morphological and molecular approaches. Prevalence rates of Blastocystis were 73% in human hosts (n=45), 100% in non-human hosts (n=44) and 91% in environmental samples (n=35). Overall, ten subtypes were identified (ST1, ST2, ST3, ST4 ST5, ST6, ST7, ST10, ST23 and ST26), eight of which were detected in humans (ST1, ST2, ST3, ST4, ST5, ST7, ST10 and ST23), three in other animals (ST6, ST7 and ST23), while seven (ST1, ST3, ST6, ST7, ST10, ST23 and ST26) were found in the environment. In our investigation of transmission dynamics, we assessed various groupings both at the household and community level. Given the overall high prevalence rate, transmission amongst humans and between animals and humans are not as frequent as expected with only two subtypes being shared. This raises questions on the role of the environment on transmission of Blastocystis. Water and soil comprise the main reservoirs of the various subtypes in this community. Five subtypes are shared between humans and the environment, while three overlap between the latter and animal hosts. We propose soil as a novel route of transmission, which should be considered in future investigations. This study provides a thorough One Health perspective on Blastocystis. Using this type of approaches advances our understanding on occurrence, diversity, ecology and transmission dynamics of this poorly understood, yet frequent gut resident.